Assessment of the Thermal Efficiency of an Indirect Solar Drying System in El Oued state - Ala taki Eddine Degachi; Mohamed Mouhadjer; Mohamed El kabir Sakhr (University of Shahid Hama Lakhdar - El Oued, 2024)
Traditionally, farmers dry their agricultural products using sunlight outdoors, including peppers, tomatoes, and others. However, this approach exposes the food to harmful changes due to UV radiation, dust pollution, insect attacks, and other factors. Dryers have been developed to overcome these issues and preserve the quality of agricultural products by achieving drying in a controlled environment inside the direct solar dryer . This study aims to mix heat storage materials with heat transfer materials (salt and aluminum). A mixture of salt and aluminum is used because salt has the ability to store heat while aluminum excels in heat transfer. This improvement was implemented in the indirect solar dryer, consisting of dedicated drying chambers well-insulated to conserve energy. Each chamber is equipped with a fan at the bottom to increase air flow, and an equal amount of salt and aluminum is placed in each chamber. Then, the thermal efficiency and storage capacities of each chamber were compared .تقليديا، يتبع المزارعون عملية الجفيف منتجاتهم الزراعية بواسطة أشعة الشمس في الهواء الطلق ، وتشمل هذه العملية الفلف ل والطماطم وغيرها، ولكن هذا النهج يعرض الطعام للتغيرات الضارة نتيجة تأثير أشعة فوق البنفسجية، والتلوث بالغبار والهجمات من الحشرات، وغيرها من العوامل تم تطوير المجفف للتغلب على هذه المشاكل والحفاظ على جودة المنتجات الزراعية عن طريق تحقيقها في بيئة محكمة الإغلاق داخل المحقق المباشر. تهدف هذه الدراسة الى خلط موا د التخزين مع مواد ناقلة للحرارة (الملح والألمنيوم) يتم استخدام خليط من الملح والألمنيوم لأن المل ح يمتلك القدرة عل ى تخزين الحرارة بينما يتميز الألمنيوم بقدرته الجيدة على نقل الحرارة تم تطبيق هذا التحسين ف ي المجفف الشمسي غير المباشر الذي يتكون من غرف مخصصة للمختص والتجفيف معزولة بشكل جيد للحفا ظ عل ى الطاق ة وتم تجهيز كل غرفة بمروحة في الجزء السفل ي الزيادة تدفق الهواء الداخل، ويتم وضع كمية متساوية من الملح والالمنيوم في كل غرفة، ثم تمت مقارنة الكفاءة الحرارية وسعات التخزين لكل غرفة
Master's theses: specializing in Renewable energies in mechanics
Keywords: direct solar dryer; indirect drying; solar energy; heat-assisted drying; salt; aluminum .; مجفف شمسي مباشر تجفيف غير مباشر طاقة شمسية تجفيف بحمل حراري، ملح، المنيوم.